Draft Annual Plan 1975-76 (Part-I) Government of Assam - Planning Commission (Planning Commission, 1975)
As per new Panchayat Raj Act, the responsibility of Subdivision level Plan formulation will lie with the Mahkuma Parishads which are an integral part of the State administrative machinery and in which specific powers and functions have been vested. The Mahkuma Parishads have full authority over the subject/schemes transferred to them and will have control over the officers connected with Implementation of developmental schemes/programmes within, their jurisdiction.
Government of Assam, Planning and Development Department